2021
DOI: 10.34172/icnj.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Iranian Students’ Mental Health: A Cross-sectional Survey

Abstract: Background: Mental health is a significant problem in developed and developing countries which influences all aspects of life. We aimed to evaluate the status of Iranian students' mental health. Methods: This cross-sectional study was performed on 2052 elementary school students located in Tehran, Iran, in September 2018. We used the Census sampling method for sampling and the general health questionnaire comprising 28 items. For statistical analysis SPSS software, version 21 was used. Results: A total of 2052… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Only 7% of participants knew the correct depth of compression during CPR in children and 6.4% in neonates. 14 A study done among medical students in Jordan showed that only 281 (31.7%) had adequate awareness, whereas 605 (68.3%) had inadequate awareness. 15 A similar study in Jordan showed that 29% of the participants had received CPR training, higher than that reported in China (33%) 16 and comparable to data reported elsewhere, including 60% in New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Only 7% of participants knew the correct depth of compression during CPR in children and 6.4% in neonates. 14 A study done among medical students in Jordan showed that only 281 (31.7%) had adequate awareness, whereas 605 (68.3%) had inadequate awareness. 15 A similar study in Jordan showed that 29% of the participants had received CPR training, higher than that reported in China (33%) 16 and comparable to data reported elsewhere, including 60% in New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their learning behaviour occupies the majority of their daily life, becoming the core of their existence. The learning attitudes, tendencies and methods displayed by students in their learning behaviours are not only applicable in the context of education but also have the potential to impact various aspects of their lives (Akhlaghdoust et al 2021). Therefore, it This study aims to explore the promoting effect of the combination of mental health education and ideological and political education for college students on improving their comprehensive psychological quality and ideological and political theoretical level.…”
Section: Introductionmentioning
confidence: 99%